Public awareness in Iceland of the long-term consequences of childhood sexual abuse - Helga Ýr Jörgensen 1998- (2022)
The difficulties that survivors of Childhood Sexual Abuse (CSA) can suffer as adults are highly variable but can be classified into mental, physical, and social consequences. Previous studies have shown that parents, especially mothers, have a good knowledge of the long-term consequences of CSA. In addition, it has been demonstrated that parents with a high-quality education have good knowledge in this field. In this study, the aim was to examine people's knowledge of the long-term consequences of CSA and to assess which groups of people require additional training in this area. The knowledge was analyzed in connection to age, gender, and educational level. The study included 326 participants. The ages varied from 18 to 75 years or older, with 48 men (14.7%) and 278 women (85.3%). The questionnaire contained background questions as well as statements about the long-term consequences of CSA, which participants had to answer whether they agreed or disagreed. One-way ANOVA and an independent sample t-test were used to interpret the study outcome. The findings revealed that men and women have about equal knowledge of the long-term consequences of CSA (M = 3.93; 3.74). People between the ages of 46 and 55 have the most knowledge, and those with only a primary school education have less knowledge than those with a higher level of education. There was a significant difference between those who knew a victim of CSA and the difficulty of dental treatment. Keywords: Knowledge, awareness, childhood sexual abuse, long-term consequences, gender, education Afleiðingarnar sem eftirlifendur kynferðislegs ofbeldis í æsku (CSA) geta orðið fyrir á fullorðinsárum eru mjög breytilegir, en hægt er að flokka þær í andlegar, líkamlegar og félagslegar afleiðingar. Fyrri rannsóknir hafa sýnt að foreldrar, sérstaklega mæður, hafa góða þekkingu á langtíma afleiðingum CSA. Ennfremur hefur komið í ljós að foreldrar með mikla menntun búa yfir góðri þekkingu á þessu sviði. Markmið þessara rannsókna var að kanna þekkingu fólks á langtíma ...